An Analysis of Some Variables as the Predictors of Children’s Overall Self-Worth Levels - Akşab, Gözde; Türk, Fulya (Psycho-Educational Research Reviews, 2022)
In this study, it was examined whether family relationship perceived by children, parental behaviors and irrational beliefs of parents predicted overall self-worth levels of children. A total of 1500 people participated in the study, including 500 students attending the 4th grade in Hatay and their parents. Personal Information Form, Parent Irrational Beliefs Scale (PIBS), Alabama Parenting Questionnaire (APQ), Family Relationship Scale for Children (FRSC) and Self-Perception Profile for Children (SPPC) were used as data collection tools in the study. In order to analyze the data, multiple linear regression analysis was conducted. According to the results obtained, there is a significant relationship between parents’ irrational beliefs, parenting behaviors, children’s perception of family relationships and general self-worth. Supportive family relationship, discouraging family relationship, unrealistic expectations of parents, father’s parental involvement, poor monitoring/supervision and corporal punishment behaviors predict the overall self-worth level of the children. The variable that significantly predicts children’s overall self-worth, on the other hand, is supportive family relationship. The results of the research were discussed in the light of the literature.